On the Credibility of the Euro/Swiss Franc Floor: A Financial Market Perspective - Markus Hertrich; Heinz Zimmermann (University of Basel, Center of Business and Economics (WWZ), 2015)
The sheer existence of EUR/CHF put options with strike prices below the EUR/CHF 1.20 floor, trading at non-zero cost, challenged the full credibility of the Swiss National Bank (SNB) in enforcing the lower barrier implemented in September 6, 2011 and abandoned on January 15, 2015. We estimate the risk-neutral break probabilities of a realignment of the floor from market prices of put options, using an extension of the Veestraeten option pricing model which assumes that the underlying security price exhibits a lower barrier. We estimate probabilities considerably different from zero, even when the exchange rate traded far above the EUR/CHF 1.20 floor. We observe a drastic increase in the break-probabilities after August 2014, reaching a level of nearly 50%. The credibility of the SNB in maintaining the floor, as seen from the option market, was thus substantially lower than publicly claimed.
Keywords: E42; E58; F31; G13; 330; currency options; central banking; credibility; Euro/Swiss franc floor; Vanna-Volga method; barrier